Fund Planning and Management Training for MSMEs Sustainability in Lembak Villages: Pelatihan Perencanaan dan Pengelolaan Dana Sebagai Upaya Keberlanjutan UMKM di Desa Lembak - John Roni Coyanda; Asmawati Asharie; Endah Dewi Purnamasari (Universitas Lancang Kuning, 2023)
MSMEs have different ways of continuing their business based on their potential. The same is true for MSMEs in Lembak Village whose types of business are kemplang crackers and plantation products such as pineapples and sweet potatoes. This business activity has been going on for a long time, of course it has more or less knowledge and ability problems that need to be improved further in efforts to end MSMEs in Lembak Village. MSME players only plan funds for a period of less than 1 year and manage their business with limited financial management capabilities. This will have an impact on the loss of MSMEs in the future. The problem faced by respondents is that there is not much knowledge about planning and managing funds. The solution needed is to provide training for MSME players. The results obtained were an increase in the ability of the respondents to plan and manage funds using accounting to end their business. The implementation is carried out using the lecture method; tutorials and discussions as well as data obtained directly through distributing pre-test and post-test questionnaires to 23 MSME respondents in Lembak Village. The final result of this service activity is very useful because it increases knowledge of the importance of planning and managing funds in efforts to stop MSMEs in Lembak Village.